Legal Assurance on the Status of Proprietary Rights to Land Destroyed Post Earthquake and Liquifaction Based on Regulation of The Minister of Agriculture Number 17 Year 2021 - Armansyah Armansyah (Eastasouth Institute, 2022)
Analysis of legal materials is carried out by tracing or inventorying primary legal materials and secondary legal materials. The next step is to identify legal materials and develop legal arguments related to the legal issues discussed. and then conclude each legal issue.To guarantee the rights to land affected by liquefaction, Article 5 of Law Number 24 of 2007 concerning Disaster Management stipulates that the Government and regional governments are responsible for the implementation of disaster management. In the elucidation of the article, what is meant by the responsibilities of the Government and regional governments in the implementation of disaster management include natural disasters, non-natural disasters, and national disasters. In this article, it is explained that the government and local governments as the person in charge of disaster management are obliged to provide guarantees for land rights affected by liquefaction.The provisions regarding destroyed land on the status of ownership of this land have been regulated in Article 27 of the LoGA, that a plot of land can be categorized as destroyed land if the land has changed from its original form due to natural events such as liquefaction. the event of the land being destroyed, does not eliminate the government''s responsibility in providing legal certainty guarantees this is based on the land parcels that cannot be functioned, used, and utilized properly. as a form of implementation of the provisions governing matters that may result in the nullification and destruction of land rights.